Resin film, laminate and packaging bag

The use of a resin film with specific elastic properties in a laminate helps to maintain the gas barrier properties of packaging materials during distribution, even under external forces like vibration.

JP2025037977APending Publication Date: 2025-03-18TOPPAN HOLDINGS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024208177
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the distribution process of packaged items, external forces such as vibration can cause deformation and lead to a deterioration of the gas barrier properties in laminates used for packaging materials.

Method used

A resin film with specific properties is used in a laminate, where the film has a transition temperature from glass to rubber state between 80°C and 88°C, and a storage elastic modulus between 3.8 GPa and 4.1 GPa, which helps in suppressing the movement and defects of the gas barrier layer under external forces.

Benefits of technology

This configuration effectively suppresses the decrease in gas barrier properties of the laminate, maintaining its suitability as a packaging material even under repeated external forces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037977000001_ABST
    Figure 2025037977000001_ABST
Patent Text Reader

Abstract

To provide a resin film which can suppress reduction in gas barrier properties in a laminate, a laminate, and a packaging bag.SOLUTION: A resin film 10 constitutes a laminate for a packaging bag by laminating a gas barrier layer having gas barrier properties. The resin film 10 contains polyethylene terephthalate, and in a storage elastic modulus curve indicating a relation between a storage elastic modulus and a temperature of the resin film 10, a transition temperature from a glassy state to a rubbery state is 80°C or higher and 88°C or lower, and a storage elastic modulus at the transfer temperature is 3.8 GPa or more and 4.1 GPa or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin film, a laminate including a resin film, and a packaging bag. [Background technology]

[0002] Resin films containing polyethylene terephthalate are widely used as packaging materials for packaging objects such as food, medicines, and cosmetics. In order to prevent deterioration of the quality of the objects, it is preferable that the packaging material has gas barrier properties that make it difficult for gases such as oxygen and water vapor to pass through. For this reason, a laminate of a resin film and a gas barrier layer including a metal film or a metal oxide film is used as the packaging material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-81607 A Summary of the Invention [Problem to be solved by the invention]

[0004] During the distribution process of a packaged product, an external force that causes deformation such as folding or twisting of the packaging material may be repeatedly applied to the product, such as when the product is subjected to vibration during transportation, etc. It is desirable that the deterioration of the gas barrier property caused by the application of such external forces is small for a laminate used as a packaging material.

[0005] An object of the present invention is to provide a resin film, a laminate, and a packaging bag that can suppress a decrease in the gas barrier property of the laminate. [Means for solving the problem]

[0006] The resin film that solves the above problem is a resin film that constitutes a laminate for packaging bags by laminating a gas barrier layer having gas barrier properties, contains polyethylene terephthalate, and in a storage elasticity curve showing the relationship between the storage elasticity of the resin film and temperature, the transition temperature from a glassy state to a rubbery state is 80°C or more and 88°C or less, and the storage elasticity at the transition temperature is 3.8 GPa or more and 4.1 GPa or less.

[0007] According to the above configuration, the strength of the elastic properties of the resin film is suitable in the environment in which the laminate is used as a packaging bag. That is, since the contribution of elasticity in the resin film in responding to an external force is not too large, even when an external force is repeatedly applied to a laminate including the resin film and a gas barrier layer, the movement of the gas barrier layer laminated on the resin film is suppressed, and the occurrence of defects in the gas barrier layer is suppressed. Therefore, the deterioration of the gas barrier properties of the laminate can be suppressed. Meanwhile, since the elastic properties of the resin film are not too weak, the deterioration of the suitability of the laminate as a packaging material is easily suppressed.

[0008] In the above-described configuration, the resin film may contain polyethylene terephthalate containing terephthalic acid and isophthalic acid in dicarboxylic acid units in the repeating units. According to the above-mentioned configuration, a resin film having a transition temperature and a storage modulus within the above-mentioned ranges can be suitably obtained.

[0009] The laminate that solves the above problem includes the above resin film and a gas barrier layer having gas barrier properties. According to the above-mentioned configuration, even when an external force is repeatedly applied, deterioration of the gas barrier property of the laminate is suppressed, and therefore the suitability of the laminate for use as a packaging material is improved.

[0010] In the above configuration, the gas barrier layer may have a first barrier layer containing at least one of aluminum oxide and silicon oxide, and a second barrier layer containing a polymer material. According to the above-mentioned configuration, the gas barrier property of the laminate is further improved.

[0011] In the above configuration, the second barrier layer may be stacked adjacent to the first barrier layer. According to the above configuration, the second barrier layer can protect the first barrier layer and complement the gas barrier properties.

[0012] In the above configuration, the second barrier layer is Si(OR 1 )4, or R 2 Si(OR 3 )3(OR 1 , OR 3 is a hydrolyzable group, R 2 is an organic functional group.) or a hydrolyzate thereof, and a water-soluble polymer having a hydroxyl group. According to the above-mentioned configuration, the effect of the second barrier layer in protecting the first barrier layer and complementing the gas barrier property is enhanced.

[0013] The packaging bag for solving the above problem is a packaging bag for packaging an object, and is made of the above laminate.

[0014] According to the above-mentioned configuration, the deterioration of the gas barrier property of the packaging bag caused by vibration during transportation of the product, etc. is suppressed, and therefore deterioration of the quality of the packaged object is suppressed. Effect of the Invention

[0015] According to the present invention, it is possible to suppress the deterioration of the gas barrier properties of the laminate. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a diagram showing a cross-sectional structure of a resin film according to an embodiment. [Diagram 2] FIG. 2 is a diagram showing a cross-sectional structure of a laminate according to an embodiment. [Diagram 3] FIG. 1 is a diagram showing a perspective structure of a packaging bag according to an embodiment. [Figure 4] FIG. 4 is a diagram showing an example of storage elasticity curves in Examples and Comparative Examples. [Diagram 5] FIG. 4 is a diagram showing an example of loss elasticity curves in an example and a comparative example. [Figure 6] FIG. 4 is a diagram showing an example of a loss tangent curve in an example and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] An embodiment of a resin film, a laminate, and a packaging bag will be described with reference to the drawings. [Resin film] The structure of the resin film 10 will be described with reference to Fig. 1. The resin film 10 contains recycled PET, which is recycled polyethylene terephthalate (PET). PET products that are subject to recycling include used PET bottles. The recycled PET contained in the resin film 10 is at least one of PET recycled by mechanical recycling and PET recycled by chemical recycling.

[0018] In mechanical recycling, PET products are crushed and washed to remove surface dirt and foreign matter, and then the resin is exposed to high temperatures to remove contaminants remaining inside the resin. In chemical recycling, PET products are crushed and washed to remove surface dirt and foreign matter, and then the resin is depolymerized to return to intermediate raw materials, which are then refined and repolymerized to produce PET. Compared to chemical recycling, mechanical recycling does not require large-scale equipment for chemical reactions, so the cost and environmental impact of producing recycled PET is small. Therefore, the recycled PET contained in the resin film 10 is preferably PET regenerated by mechanical recycling.

[0019] In addition to recycled PET, the resin film 10 may contain virgin PET, which is PET newly synthesized from raw materials such as petroleum. The mass ratio of recycled PET contained in the resin film 10 is preferably 60% or more and 100% or less of the total mass of the resin film 10.

[0020] The repeating units of PET include diol units and dicarboxylic acid units. In a resin film for packaging applications made of virgin PET, the diol units are ethylene glycol, and the dicarboxylic acid units are terephthalic acid. On the other hand, in the dicarboxylic acid raw material of PET used in PET bottles, isophthalic acid is mixed in addition to terephthalic acid in order to improve the processability of the resin when molding it into a bottle shape. That is, in PET bottles, the diol units are ethylene glycol, and the dicarboxylic acid units include terephthalic acid and isophthalic acid. The inclusion of isophthalic acid suppresses crystallization of PET, improving processability. The diol units may include diethylene glycol.

[0021] Therefore, the dicarboxylic acid units of the recycled PET contain terephthalic acid and isophthalic acid. That is, the resin film 10 contains PET having dicarboxylic acid units containing terephthalic acid and isophthalic acid. The proportion of isophthalic acid in the total dicarboxylic acid units of the PET contained in the resin film 10 is preferably 0.5 mol % or more and 5 mol % or less.

[0022] The average molecular weight of the PET contained in the resin film 10 is not particularly limited, but is preferably, for example, about 1,000 to 1,000,000. The resin film 10 may contain resins other than PET and various additives such as plasticizers.

[0023] The resin film 10 may be composed of a single layer, or may be a laminate of multiple layers. When the resin film 10 has multiple layers, the layers of the resin film 10 may have the same composition, or the layers of the resin film 10 may include layers of different compositions. For example, the layers of the resin film 10 may include a layer made of recycled PET and a layer made of virgin PET. Alternatively, the layers of the resin film 10 may include multiple layers containing recycled PET in different ratios.

[0024] The thickness of the resin film 10 is selected depending on various resistances and processability required for the packaging bag. From the viewpoint of processability, the thickness of the resin film 10 is preferably 3 μm or more and 100 μm or less, and more preferably 6 μm or more and 50 μm or less, in practical terms.

[0025] There is no particular limitation on the method for forming the resin film 10, and any known film forming method such as extrusion molding may be used. Furthermore, as the method for extrusion and cooling, any known cooling method such as cooling rolls, air cooling, water cooling, etc. may be used. Furthermore, the resin film 10 may be produced without stretching or by stretching. As the stretching method, a known stretching method such as uniaxial stretching or biaxial stretching is used.

[0026] [Laminate] The structure of the laminate 20 will be described with reference to Fig. 2. The laminate 20 includes a resin film 10 and a gas barrier layer 11. The gas barrier layer 11 has a function of enhancing the gas barrier properties of the laminate 20.

[0027] The gas barrier layer 11 includes a first barrier layer made of, for example, an inorganic oxide or a metal. The inorganic oxide is, for example, an oxide of silicon, aluminum, magnesium, calcium, potassium, tin, sodium, boron, titanium, lead, zirconium, yttrium, or the like. The metal is, for example, an oxide of aluminum, magnesium, tin, sodium, titanium, lead, zirconium, yttrium, gold, chromium, or the like. The first barrier layer may include two or more of these materials.

[0028] When a transparent packaging bag is formed from the laminate 20, a first barrier layer made of an inorganic oxide is used. In particular, a first barrier layer made of aluminum oxide or silicon oxide is preferably used. When a light-shielding property is to be imparted to the packaging bag formed from the laminate 20, a first barrier layer made of a metal is used. In particular, a first barrier layer made of aluminum is preferably used. The gas barrier layer 11 may include a plurality of first barrier layers made of the same or different materials.

[0029] The thickness of the first barrier layer is selected depending on the material of the first barrier layer, etc. The thickness of the first barrier layer is preferably 5 nm or more and 300 nm or less, and more preferably 10 nm or more and 150 nm or less. If the thickness of the first barrier layer is equal to or more than the above lower limit, the first barrier layer is easily formed into a uniform film, and the thickness of the first barrier layer is sufficiently ensured, so that good gas barrier properties are obtained. If the thickness of the first barrier layer is equal to or less than the above upper limit, the flexibility of the first barrier layer is well obtained, so that the occurrence of cracks in the first barrier layer due to external factors such as bending or pulling the laminate 20 is easily suppressed.

[0030] The first barrier layer can be formed on the substrate by vacuum deposition, sputtering, ion plating, plasma vapor deposition (CVD), etc. In particular, the vacuum deposition is preferably used from the viewpoint of increasing productivity. As the heating means for the vacuum deposition, it is preferable to use any one of the electron beam heating method, the resistance heating method, and the induction heating method, but it is more preferable to use the electron beam heating method from the viewpoint of a high degree of freedom in selecting the evaporation material. In addition, in order to improve the adhesion between the first barrier layer and the substrate and the denseness of the first barrier layer, it is also possible to perform deposition using a plasma assist method or an ion beam assist method. In addition, in order to increase the transparency of the first barrier layer, reactive deposition may be used in which various gases such as oxygen are blown in during deposition.

[0031] When the first barrier layer is formed on the resin film 10, the surface of the resin film 10 may be subjected to a surface treatment such as a plasma treatment or a corona treatment in order to improve the adhesion between the resin film 10 and the first barrier layer. Also, an anchor coat layer may be formed between the resin film 10 and the first barrier layer in order to improve the adhesion between these layers. These configurations improve the performance of the laminate 20, such as the adhesion between the layers and the gas barrier property after heat sterilization.

[0032] The gas barrier layer 11 may include a second barrier layer containing a polymer material in addition to the first barrier layer or instead of the first barrier layer. For example, a second barrier layer may be laminated on the first barrier layer made of an inorganic oxide in order to protect the first barrier layer and complement the gas barrier properties of the first barrier layer. In this case, the laminate 20 has a structure in which the first barrier layer and the second barrier layer are laminated in this order on the resin film 10. The first barrier layer and the second barrier layer are adjacent to each other. The material of the second barrier layer may be selected depending on the purpose of forming the second barrier layer. Below, a configuration suitable for the second barrier layer for protecting the above-mentioned first barrier layer and complementing the gas barrier properties will be described.

[0033] The second barrier layer contains a water-soluble polymer and an inorganic compound. The water-soluble polymer has a hydroxyl group. Examples of the water-soluble polymer include polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, and sodium alginate. In particular, polyvinyl alcohol (PVA) is preferable because it is excellent in improving gas barrier properties.

[0034] The inorganic compound contained in the second barrier layer is Si(OR 1 )4, or R 2 Si(OR 3 )3(OR 1 , OR 3 is a hydrolyzable group, R 2 is an organic functional group. The second barrier layer may contain two or more of the above silicon compounds or their hydrolysates. Si(OR1 As the silane, tetraethoxysilane [Si(OC2H5)4] is preferably used because it is relatively stable in aqueous solvents after hydrolysis. 2 Si(OR 3 )R in 3 2 is preferably selected from the group consisting of a vinyl group, an epoxy group, a methacryloxy group, a ureido group, and an isocyanate group.

[0035] The second barrier layer is formed by applying a mixed solution of the materials of the second barrier layer. The mixed solution is prepared by mixing a silicon compound directly or by hydrolyzing the silicon compound in a solution obtained by dissolving a water-soluble polymer in water or a mixed solvent of water and alcohol. The mixed solution is applied onto the first barrier layer, and the formed coating film is then heated and dried to form the second barrier layer. The mixed solution may contain known additives such as an isocyanate compound, a silane coupling agent, a dispersant, a stabilizer, a viscosity modifier, and a colorant, as necessary, within the range that does not impair the gas barrier properties.

[0036] When PVA is used as the water-soluble polymer, the ratio of PVA in the mixed solution is preferably 20 wt% to 50 wt%, and more preferably 25 wt% to 40 wt%, of the total solid content of the mixed solution. If the ratio of PVA is equal to or greater than the lower limit, the second barrier layer can have good flexibility, making it easy to form the second barrier layer. If the ratio of PVA is equal to or less than the upper limit, the second barrier layer can have good gas barrier properties. The thickness of the second barrier layer is selected, for example, from the range of 0.05 μm to 30 μm.

[0037] In addition, the gas barrier layer 11 may include a layer made of another material, such as a metal nitride, in addition to the first barrier layer and the second barrier layer, or instead of the first barrier layer and the second barrier layer.

[0038] In addition to the resin film 10 and the gas barrier layer 11, the laminate 20 may include a sealing layer containing a thermoplastic resin, an adhesive layer for improving adhesion between the gas barrier layer 11 and an upper or lower layer, a layer for decoration or displaying information formed by printing, etc. The sealing layer is melted when forming a packaging bag in which the ends of the laminate 20 are fused together by heat sealing.

[0039] The thickness of the laminate 20 is, for example, 30 μm or more and 300 μm or less. The thickness of the laminate 20 may be selected depending on various resistances and processability required for the packaging bag. The laminate 20 may be formed by various physical vapor deposition methods, various coating methods, dry lamination, extrusion lamination, or the like, depending on the materials of the gas barrier layer 11 and other layers.

[0040] [Packaging bag] The configuration of the packaging bag 30 will be described with reference to Fig. 3. The packaging bag 30 has a bag shape formed from the laminate 20 and is configured to be sealable. In the packaging bag 30, the gas barrier layer 11 is located on the inner side of the resin film 10. The shape and size of the packaging bag 30 are not particularly limited, and may be designed according to the object to be packaged. The object to be packaged is, for example, food, medicine, cosmetics, etc.

[0041] The method for joining the ends of the laminate 20 when forming the packaging bag 30 is not particularly limited, and heat sealing may be used as described above, or the ends of the laminate 20 may be joined by other methods. Fig. 3 illustrates an example of a form in which the packaging bag 30 has a sealed portion 31 at its end where the ends of the laminate 20 are joined.

[0042] [Physical properties of resin film] The inventors of the present application have found that the flexibility of the resin film 10 contributes to suppressing a decrease in the gas barrier property of the laminate 20. The inventors of the present application have focused on dynamic elastic moduli, that is, the storage elastic modulus G1, the loss elastic modulus G2, and the loss tangent (tan δ), as parameters for evaluating the flexibility of the resin film 10.

[0043] When an external force due to vibration or the like is applied to the laminate 20, the gas barrier layer 11 deforms in accordance with the deformation of the resin film 10. The storage modulus G1 indicates the component of energy generated by stress in an object that is stored inside the object, and the loss modulus G2 indicates the component of the energy that is diffused to the outside as heat. That is, the magnitude of the storage modulus G1 indicates the strength of the properties of the resin film 10 as an elastic body, and the magnitude of the loss modulus G2 indicates the strength of the properties of the resin film 10 as a viscous body. Tan δ is the ratio (G2 / G1) of the loss modulus G2 to the storage modulus G1, and indicates the balance between the properties of the resin film 10 as an elastic body and the properties of the viscous body.

[0044] The stronger the elastic properties of the resin film 10, the higher the responsiveness of the shape change to the application and release of an external force. That is, when the application and release of an external force to the resin film 10 is repeated in a short period of time, such as when the resin film 10 is subjected to vibration, the generation of strain due to the application of the external force and the recovery of the strain due to the release of the external force are repeated in the resin film 10 in a short period of time. Therefore, the movement of the gas barrier layer 11 following the resin film 10 becomes large, and as a result, defects such as pinholes are easily generated in the gas barrier layer 11, and the gas barrier property of the laminate 20 is easily deteriorated.

[0045] On the other hand, when the resin film 10 has stronger viscous properties, the progress of deformation in response to the application of an external force becomes slower, and the deformation is less likely to return to its original state even when the external force is released. Therefore, even when the application and release of an external force to the resin film 10 is repeated in a short period of time, the movement of the resin film 10 and the gas barrier layer 11 is suppressed. In other words, the laminate 20 has higher vibration absorption properties. Therefore, the occurrence of defects in the gas barrier layer 11 is suppressed, and the deterioration of the gas barrier properties of the laminate 20 is suppressed.

[0046] However, if the viscous properties of the resin film 10 become too strong, the suitability of the laminate 20 as a packaging material, such as ease of processing and strength, decreases. As a result of extensive research, the inventors of the present application have found ranges of the storage modulus G1, loss modulus G2, and tan δ of the resin film 10 that can suppress a decrease in gas barrier properties while maintaining the suitability of the laminate 20 as a packaging material. The preferred ranges of each parameter are described below.

[0047] In the storage elasticity curve showing the relationship between the storage elastic modulus G1 and temperature of the resin film 10, the transition temperature T1 from the glassy state to the rubbery state is 80°C or higher and 88°C or lower, and the storage elastic modulus G1 at the transition temperature T1 is 3.8 GPa or higher and 4.1 GPa or lower.

[0048] The temperature of the environment in which the packaging bag 30 is used is often lower than the transition temperature T1, that is, the resin film 10 is used in a glassy state with low fluidity. Since the change in the storage modulus G1 when the resin film 10 is in a glassy state is small, the elastic properties of the resin film 10 when it is used as the packaging bag 30 can be appropriately evaluated by evaluating the storage modulus G1 at the transition temperature T1.

[0049] If the storage modulus G1 at the transition temperature T1 is 4.1 GPa or less, the contribution of elasticity in the resin film 10 in responding to an external force does not become too large, thereby suppressing a decrease in the gas barrier properties of the laminate 20. On the other hand, if the storage modulus G1 at the transition temperature T1 is 3.8 GPa or more, the properties of the resin film 10 as an elastic body do not become too weak, so that a decrease in the suitability of the laminate 20 as a packaging material is likely to be suppressed.

[0050] In the loss modulus curve showing the relationship between the loss modulus G2 and temperature of the resin film 10, it is preferable that the temperature T2 at the peak position is 95°C or more and 102°C or less, and the loss modulus G2 at the peak position is 0.30 GPa or more and 0.37 GPa or less.

[0051] The temperature T2 at the peak position in the loss elasticity curve is the temperature at which the viscous properties of the resin film 10 are significantly expressed. The higher the temperature T2, the less flexibility due to viscosity tends to be exhibited in the low temperature range including the temperature of the environment in which the packaging bag 30 is used. If the temperature T2 is 102°C or lower and the loss modulus G2 at the peak position, i.e., the loss modulus G2 at the temperature T2, is 0.30 GPa or higher, flexibility due to viscosity is likely to be exhibited well in the low temperature range. Therefore, the deterioration of the gas barrier property of the laminate 20 is suppressed. Furthermore, if the loss modulus G2 at the peak position is 0.37 GPa or less, the deterioration of the suitability of the laminate 20 as a packaging material is likely to be suppressed.

[0052] In the loss tangent curve showing the relationship between tan δ and temperature of the resin film 10, tan δ at the peak position is preferably 0.160 or more and 0.190 or less. The temperature T3 at the peak position is preferably 108°C or more and 115°C or less.

[0053] Since tan δ is the ratio of the storage modulus G1 to the loss modulus G2, the influence of factors for each sample of the resin film 10 that cause errors in the dynamic modulus is eliminated. In other words, there is little variation in the curve shape between samples having the same configuration. Therefore, by using tan δ, it is possible to accurately evaluate the dynamic modulus.

[0054] The larger the tan δ, the greater the viscous properties of the resin film 10 relative to its elastic properties, i.e., the greater the vibration absorption. If the tan δ at the peak position is 0.160 or more, the ratio of the contribution of viscosity to the contribution of elasticity in the response to an external force in the resin film 10 is sufficiently large, so that a decrease in the gas barrier properties of the laminate 20 is suppressed. On the other hand, if the tan δ at the peak position is 0.190 or less, the viscous properties of the resin film 10 relative to its elastic properties are not too great, so that a decrease in the suitability of the laminate 20 as a packaging material is suppressed.

[0055] Furthermore, if the temperature T3 at the peak position is 115° C. or lower, the flexibility of the resin film 10 due to its viscosity is likely to be exhibited satisfactorily in a low temperature range that includes the temperature of the environment in which the packaging bag 30 is used.

[0056] The values ​​of the storage modulus G1, loss modulus G2, and tan δ at each temperature T1, T2, and T3 can be adjusted by the composition of the resin film 10, the temperature and speed of extrusion and cooling, the stretching ratio, and other manufacturing conditions. For example, the higher the ratio of isophthalic acid to the total dicarboxylic units of the PET contained in the resin film 10, the more the molecular orientation is hindered, the greater the flexibility of the resin film 10 is, and the stronger the properties of the resin film 10 as a viscous body can be. In terms of cooling temperature, a lower cooling temperature during the production of the resin film 10 can reduce the storage modulus G1 and increase tan δ. As a result, the flexibility of the resin film 10 is increased even in the low temperature range, and the stronger the properties of the resin film 10 as a viscous body can be. In terms of cooling rate, rapid cooling rather than slow cooling can cause the resin to grow crystals appropriately while leaving amorphous parts, so that the temperature T3 is lower, but tan δ and the loss modulus G2 can be increased. As a result, the flexibility of the resin film 10 is increased, and the properties of the resin film 10 as a viscous body can be strengthened. In terms of the stretching ratio, by reducing the stretching ratio during the production of the resin film 10, molecular orientation can be suppressed, so that the transition temperature T1 can be lowered and an increase in the storage modulus G1 can be suppressed. As a result, the flexibility of the resin film 10 is increased, and the properties of the resin film 10 as a viscous body can be strengthened.

[0057] [Example] The above-mentioned resin film and laminate will be described using specific examples and comparative examples.

[0058] Example 1 Three resin layers were laminated by coextrusion to form the resin film of Example 1. Each resin layer is a layer in which recycled PET regenerated by mechanical recycling and virgin PET are mixed. The three resin layers have the same composition. The mass ratio of recycled PET contained in the resin film of Example 1 is 80% of the total mass of the resin film. The thickness of the resin film of Example 1 is 12 μm.

[0059] A first barrier layer made of aluminum oxide was laminated on the resin film of Example 1 by using a vacuum deposition method. The thickness of the first barrier layer was 10 nm. Furthermore, a second barrier layer was formed on the first barrier layer by using a direct gravure coating method. In detail, a mixed solution for forming the second barrier layer was prepared by mixing a hydrolysis solution obtained by adding hydrochloric acid to tetraethoxysilane and stirring for 30 minutes to hydrolyze it, and a PVA solution obtained by dissolving polyvinyl alcohol in a mixed solvent of water and isopropyl alcohol at a ratio of 60:40. The mixed solution was applied onto the first barrier layer by using a bar coater, and the formed coating film was dried at 120°C for 1 minute by using a dryer to form a second barrier layer. The thickness of the second barrier layer was 300 nm. This resulted in the production of the laminate of Example 1. That is, the laminate of Example 1 included a resin film and a gas barrier layer including a first barrier layer and a second barrier layer.

[0060] Example 2 The resin film of Example 2 was formed by laminating three resin layers so that the second resin layer was sandwiched between two first resin layers. The first resin layer is a layer made of recycled PET regenerated by chemical recycling. The second resin layer is a layer in which recycled PET regenerated by mechanical recycling is mixed with a small amount of recycled PET regenerated by chemical recycling. The mass ratio of recycled PET contained in the resin film of Example 2 is 100% of the total mass of the resin film. The thickness of the resin film of Example 2 is 12 μm.

[0061] Example 3 The resin film of Example 3 was formed by laminating three resin layers so that the second resin layer was sandwiched between two first resin layers. The first resin layer was a layer made of virgin PET. The second resin layer was a layer made of recycled PET regenerated by chemical recycling. The mass ratio of the recycled PET contained in the resin film of Example 3 was 70% of the total mass of the resin film. The thickness of the resin film of Example 3 was 12 μm.

[0062] (Comparative Example) A resin film of the comparative example was obtained by forming one resin layer made of virgin PET. The resin film of the comparative example did not contain recycled PET. The thickness of the resin film of the comparative example was 12 μm.

[0063] A comparative laminate was obtained by laminating a first barrier layer and a second barrier layer to the resin film of the comparative example using the same materials and method as in Example 1. That is, the comparative laminate includes a resin film and a gas barrier layer having the same configuration as in Example 1.

[0064] <Measurement of dynamic elastic modulus> A strip-shaped test piece was prepared from the resin film of each Example and Comparative Example. The length of the test piece was 20 mm, and the width of the test piece was 10 mm. The flow direction (MD direction) during the formation of the resin film was set as the length direction of the test piece. The storage modulus G1 and loss modulus G2 of each test piece were measured using a thermomechanical analyzer (Hitachi High-Tech Science: DMA7100), and tan δ was calculated. The measurement conditions were as follows. Frequency: 10Hz Tension condition: Strain amplitude 10μm : Minimum tension / compression force 50mN :Tension / Compression Gain 1.2 : Initial force amplitude 50mN Heating conditions: Heating rate 2℃ / min :Heating temperature 30℃~180℃

[0065] <Gas barrier property evaluation> Test pieces were prepared from the laminates of Example 1 and Comparative Example, and a Gelbo Flex test was carried out to evaluate the flexibility of the laminates. The test method is described below. Then, to evaluate the gas barrier properties of the laminates, the oxygen permeability and water vapor permeability were measured for the laminates before and after the Gelbo Flex test. The measurement method is described below.

[0066] (Flexibility evaluation) The flexibility of the laminate was evaluated using a flexibility evaluation device (Gelbo Flex Tester, manufactured by Tester Sangyo Co., Ltd.). First, a test piece was attached to the fixed head of the evaluation device so as to be cylindrical. Next, while holding both ends of the test piece, the laminate was bent by repeating the operation of twisting 440 degrees with an initial gripping distance of 175 mm and a stroke of 87.5 mm 10 times at a speed of 40 times / min.

[0067] (Measurement of water vapor permeability) The water vapor permeability of the laminate was measured using a water vapor permeability measuring device (PERMATRAN 3 / 31, manufactured by Modern Control) under conditions of a temperature of 40° C. and a relative humidity of 90%. The measurement method was in accordance with JIS K-7129 and ASTM F1249-90, and the unit of measurement was [g(STP) / m 2 -day].

[0068] (Oxygen permeability measurement) The oxygen permeability of the laminate was measured using an oxygen permeability measuring device (OXTRAN 2 / 20, manufactured by Modern Control) under conditions of a temperature of 30° C. and a relative humidity of 70%. The measurement method was in accordance with JIS K-7126 B method (constant pressure method) and ASTM D3985-81, and the unit of measurement was [cm 3 (STP) / m 2 ·day·MPa].

[0069] <Measurement results> Figures 4 to 6 show curves obtained by measuring the dynamic modulus of elasticity for the resin films of each Example and Comparative Example. Figure 4 shows a storage elasticity curve, Figure 5 shows a loss elasticity curve, and Figure 6 shows a loss tangent curve. The dynamic modulus of elasticity was measured for three test pieces for each Example and Comparative Example. The curves shown in Figures 4 to 6 show representative curves among the curves obtained by measuring the three test pieces.

[0070] Table 1 shows the analysis results of the storage elasticity, loss elasticity, and tan δ for the resin films of each of the Examples and Comparative Examples. Each value of the analysis results is the average value obtained from measurements on three test pieces.

[0071] The analytical values ​​of storage elasticity are the transition temperature T1 in the storage elasticity curve and the storage elastic modulus G1 at the transition temperature T1. The transition temperature T1 was determined as the temperature at the intersection of the approximation line of the glass region, which is on the lower side of the inflection point in the storage elasticity curve, and the approximation line of the transition region, which is on the higher side of the inflection point. The approximation line on the low-temperature side was created by approximating the group of measurement points between the inflection point and a point about 10 degrees lower to a point about 5 degrees lower than the inflection point. The approximation line on the high-temperature side was created by approximating the group of measurement points between the inflection point and a point about 5 degrees higher to a point about 10 degrees higher than the inflection point.

[0072] The analytical value of loss modulus is the temperature T2 and loss modulus G2 at the peak position in the loss modulus curve. The analytical value of tan δ is the temperature T3 and tan δ at the peak position in the loss tangent curve.

[0073] Table 2 shows the measurement results of oxygen permeability and water vapor permeability for the laminates of Example 1 and Comparative Example. For Example 1 before the Gelbo Flex test, and for Example 1 and Comparative Example after the Gelbo Flex test, the permeability was measured for two test pieces, and the average value was calculated.

[0074] [Table 1]

[0075] [Table 2]

[0076] As shown in Table 1, in Examples 1 to 3 containing recycled PET, the transition temperature T1 in the storage elasticity curve is 80° C. or more and 88° C. or less, and the storage elastic modulus G1 at the transition temperature T1 is 3.8 GPa or more and 4.1 GPa or less. On the other hand, the storage elastic modulus G1 of the comparative example not containing recycled PET is greater than 4.1 GPa. That is, it is suggested that the resin film of the comparative example has stronger elastic properties than the resin films of Examples 1 to 3.

[0077] In addition, in Examples 1 to 3, the temperature T2 at the peak position in the loss elasticity curve is 95°C or more and 102°C or less, and the loss modulus G2 at the peak position is 0.30GPa or more and 0.37GPa or less. On the other hand, the temperature T2 of the comparative example is greater than 102°C. That is, it is suggested that the resin film of the comparative example is difficult to exhibit flexibility due to viscosity in the low temperature region. Note that, although the loss modulus G2 at the peak position of the comparative example is greater than 0.37, the difference in the loss modulus G2 is small compared to the difference in the storage modulus G1 between the examples and the comparative example, and it is difficult to say that the properties as a viscous body are significantly stronger in the comparative example.

[0078] In addition, in Examples 1 to 3, the temperature T3 at the peak position in the loss tangent curve is 108°C or more and 115°C or less, and the tan δ at the peak position is 0.160 or more and 0.190 or less. On the other hand, the tan δ at the peak position in the comparative example is smaller than 0.160. That is, compared to Examples 1 to 3, it is suggested that the comparative example has a smaller viscous body property relative to the elastic body property, and the contribution ratio of viscosity in response to external force is smaller. In addition, the temperature T3 in the comparative example is larger than 115°C, suggesting that the resin film of the comparative example has difficulty in exhibiting flexibility in the low temperature region.

[0079] As shown in Table 2, Example 1 shows a smaller decrease in oxygen permeability before and after the Gelbo flex test than the comparative example. Also, Example 1 shows a smaller decrease in water vapor permeability before and after the Gelbo flex test than the comparative example. Therefore, it was confirmed that Example 1 suppresses the decrease in gas barrier property before and after the Gelbo flex test more than the comparative example. In other words, it was shown that if each parameter of storage elasticity, loss elasticity, and tan δ is within the above range, the flexibility of the resin film 10 can be suitably obtained, and as a result, the decrease in gas barrier property of the laminate against the application of an external force can be suppressed.

[0080] As described above in the embodiments and examples, the resin film, laminate, and packaging bag can provide the following effects. (1) In the storage elasticity curve of the resin film 10, the transition temperature T1 is 80°C or more and 88°C or less, and the storage elastic modulus G1 at the transition temperature T1 is 3.8 GPa or more and 4.1 GPa or less. This makes the strength of the properties of the resin film 10 as an elastic body suitable in the environment in which the packaging bag 30 is used. That is, since the contribution of the elasticity of the resin film 10 in response to an external force is not too large, even if an external force is repeatedly applied to the laminate 20, the movement of the gas barrier layer 11 laminated on the resin film 10 is suppressed, and the occurrence of defects in the gas barrier layer 11 is suppressed. Therefore, the deterioration of the gas barrier property of the laminate 20 can be suppressed. On the other hand, since the properties of the resin film 10 as an elastic body are not too weak, the deterioration of the suitability of the laminate 20 as a packaging material is easily suppressed.

[0081] (2) In the loss elasticity curve of the resin film 10, the temperature T2 at the peak position is 95°C or more and 102°C or less, and the loss elastic modulus G2 at the peak position is 0.30 GPa or more and 0.37 GPa or less. This makes it easy for the resin film 10 to exhibit good flexibility due to its viscosity in a low temperature range that includes the temperature of the environment in which the packaging bag 30 is used. This prevents a decrease in the gas barrier properties of the laminate 20. In addition, since the properties of the resin film 10 as a viscous body are not too strong, a decrease in the suitability of the laminate 20 as a packaging material is easily prevented.

[0082] (3) The tan δ at the peak position in the loss tangent curve of the resin film 10 is 0.160 or more and 0.190 or less. This provides an appropriate ratio of the properties of the resin film 10 as a viscous body relative to the properties of the elastic body. That is, in the resin film 10, the ratio of the contribution of viscosity to the contribution of elasticity in responding to an external force becomes sufficiently large, so that the vibration absorption is improved. This makes it possible to suppress a decrease in the gas barrier property of the laminate 20. In addition, the temperature T3 at the peak position in the loss tangent curve of the resin film 10 is 108°C or more and 115°C or less. This makes it possible for the resin film 10 to exhibit good flexibility due to viscosity in the environment in which the packaging bag 30 is used, since the temperature T3 at the peak position is not too high.

[0083] (4) The laminate 20 including the resin film 10 and the gas barrier layer 11 can suppress deterioration of the gas barrier properties of the laminate 20 even when external force is repeatedly applied. This improves the suitability of the laminate 20 for use as a packaging material.

[0084] (5) The gas barrier layer 11 has a first barrier layer containing at least one of aluminum oxide and silicon oxide, and a second barrier layer containing a polymer material, thereby improving the gas barrier properties of the laminate 20.

[0085] (6) Since the second barrier layer is laminated adjacent to the first barrier layer, the second barrier layer can protect the first barrier layer and complement the gas barrier properties. (7) The second barrier layer is Si(OR 1 )4, or R 2 Si(OR 3 )3(OR 1 , OR 3 is a hydrolyzable group, R 2 is an organic functional group. By containing one or more silicon compounds represented by the formula (I) or hydrolysates thereof, and a water-soluble polymer having a hydroxyl group, the effect of the second barrier layer in protecting the first barrier layer and complementing the gas barrier property is enhanced.

[0086] (8) The packaging bag 30 made of the laminate 20 prevents the gas barrier properties of the packaging bag 30 from deteriorating due to vibration during transportation of the product, and therefore prevents deterioration in the quality of the packaged object. [Explanation of symbols]

[0087] 10...Resin film 11...Gas barrier layer 20...Laminate 30...Packaging bag

Claims

1. A resin film that constitutes a laminate for a packaging bag by laminating a gas barrier layer having gas barrier properties, The recycled polyethylene terephthalate is at least one of mechanically recycled polyethylene terephthalate and chemically recycled polyethylene terephthalate, In a storage elasticity curve showing the relationship between the storage elastic modulus and temperature of the resin film, the transition temperature from a glass state to a rubber state is 80° C. or more and 88° C. or less, and the storage elastic modulus at the transition temperature is 3.8 GPa or more and 4.1 GPa or less. Resin film.

2. The mass ratio of the recycled polyethylene terephthalate contained in the resin film is 70% or more of the total mass of the resin film. The resin film according to claim 1 .

3. The recycled polyethylene terephthalate contains terephthalic acid and isophthalic acid in the dicarboxylic acid units in the repeating units. The resin film according to claim 1 or 2.

4. The proportion of isophthalic acid in the total dicarboxylic acid units of polyethylene terephthalate contained in the resin film is 0.5 mol % or more and 5 mol % or less. The resin film according to claim 3.

5. The resin film according to any one of claims 1 to 4, A gas barrier layer having gas barrier properties; A laminate comprising:

6. the gas barrier layer is an inorganic oxide vapor deposition layer or a metal vapor deposition layer, The inorganic oxide vapor deposition layer is made of any one of oxides of silicon, aluminum, magnesium, calcium, potassium, tin, sodium, boron, titanium, lead, zirconium, and yttrium; The metal deposition layer is made of any one of aluminum, magnesium, tin, sodium, titanium, lead, zirconium, yttrium, gold, and chromium. The laminate according to claim 5.

7. The gas barrier layer is a first barrier layer comprising at least one of aluminum oxide, silicon oxide, and aluminum; and a second barrier layer comprising a polymeric material. The laminate according to claim 5.

8. The second barrier layer is laminated adjacent to the first barrier layer. The laminate according to claim 7.

9. The second barrier layer is Si(OR 1 ) 4 , or R 2 Si(OR 3 ) 3 (OR 1 , OR 3 is a hydrolyzable group, R 2 is an organic functional group.) or one or more silicon compounds represented by the formula (I) or their hydrolyzates, and a water-soluble polymer having a hydroxyl group. The laminate according to claim 7 or 8.

10. The thickness of the laminate is 30 μm or more and 300 μm or less. The laminate according to any one of claims 5 to 9.

11. A packaging bag for packaging an object, The laminate according to any one of claims 5 to 10 is formed. packaging bag.

Citation Information

Patent Citations

  • Transparent gas barrier laminate

    JP2006007566A

  • Laminate

    JP2019006082A

  • Laminated multilayer body and packing bag made of the same

    JP2019081607A